2001
DOI: 10.4049/jimmunol.166.10.6000
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Induces CD86 Expression and Chemokine Production by Human Immature Dendritic Cells

Abstract: Mast cells and immature dendritic cells (DC) are in close contact in peripheral tissues. Upon activation, mast cells release histamine, a mediator involved in the immediate hypersensitivity reaction. We therefore tested whether histamine could affect human DC activation and maturation. Histamine induces CD86 expression on immature DC in a dose-dependent (significant at 10−7 M) and transient manner (maximal after 24-h stimulation). Histamine also transiently up-regulates the expression of the costimulatory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
132
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(145 citation statements)
references
References 53 publications
8
132
0
5
Order By: Relevance
“…However, there was a slight trend toward reduced LC numbers in the activated LNs, which may reflect some cross-inhibition of H2 receptors by the relatively high doses of pyrilamine used in this study. Histamine up-regulates the expression of CD86, CD40, CD54, CD80, and MHC class II, as well as induces proinflammatory cytokine and chemokine production by human immature dendritic cells through H1 and H2 receptors (11). However, histamine alone does not up-regulate CCR7, which is thought to be crucial for dendritic cell migration and can be regulated by IL-1␤ or TNF (40,41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there was a slight trend toward reduced LC numbers in the activated LNs, which may reflect some cross-inhibition of H2 receptors by the relatively high doses of pyrilamine used in this study. Histamine up-regulates the expression of CD86, CD40, CD54, CD80, and MHC class II, as well as induces proinflammatory cytokine and chemokine production by human immature dendritic cells through H1 and H2 receptors (11). However, histamine alone does not up-regulate CCR7, which is thought to be crucial for dendritic cell migration and can be regulated by IL-1␤ or TNF (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has also demonstrated that mast cell-derived TNF is primarily responsible for LN swelling following bacterial or compound 48/80-induced mast cell activation (20), while histamine did not contribute significantly to this response. Dendritic cells have, however, been shown to express H1, H2, and H3 receptors and to undergo significant maturational changes as a result of histamine treatment (11,(21)(22)(23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of H1R and H2R on human monocyte-derived DC (MoDC) has also recently been reported (10 -13), and stimulation of MoDC with histamine resulted in induction of CD86 surface expression (14), suppression of IL-12 production (10 -13), and polarization of DC into Th2 cell promoting cells (10,13).…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%
“…There were also some modulated genes with important anti-inflammatory properties in 6-dpf fish: the histamine receptor H2 (HRH2), that acts as a suppressor of antigen presentation capacity and enhances IL10 production [58][59][60][61][62][63] and the toll IL1 receptor domain-containing adaptor (SARM1) that down-modulates NFKB and IRF3-mediated TLR3 and TLR4 signaling. 64 Similar to the LD treatment, some proteins related to tissue damage and apoptosis were also modulated in zebrafish in response to the SLD treatment, but the inflammatory effects did not seem to be as apparent as for the lethal treatment.…”
Section: Dios Et Almentioning
confidence: 99%